RUANG TUMBUH UNTUK PENYU DAN TERUMBU KARANG DENGAN METODE KAMUFLASE - Bernadette Adelia Oktaviani; Franky Liauw (Jurusan Arsitektur dan Perencanaan, 2021)
Indonesia as an archipelago country is influenced and influences the sea. The condition of the sea in Indonesia greatly affects the marine ecosystem, both in flora and fauna. Sea turtles and coral reefs are representatives of flora and fauna that are affected by the marine ecosystem. Most type of sea turtles can be found in Indonesia and Indonesia is located in the coral triangle so there is high coral reef diversification. However, this condition is often being neglected by the tourists and fishermen. This project is a conservation facility to increase the growth of sea turtles and coral reefs and complemented by tourism activities as an effort to increase visitors and awareness of the importance of sea turtles and coral reefs for marine ecosystems. This project is located in Kelapa Dua Island, Thousand Islands, North Jakarta. In this project the design method applied is camouflage, this method is chosen to increase comfortability for the sea turtles during their nesting process in the coastal area. From this method, there are several important points such as nature, vegetation, vision, shape, and color. Its application based on this method can be seen through the natural materials that are used in this building so it blends with the surrounding environment, vegetation to increase the potential for turtles to lay eggs and camouflaging the building, and curved shapes to mimic turtles. Therefore, it can increase the love and human consciousness of nature. Keywords: camouflage; coral reef; marine ecosystem; sea turtleAbstrakIndonesia sebagai negara kepulauan sangat dipengaruhi dan mempengaruhi perairan di sekitarnya. Kondisi perairan di Indonesia sangat mempengaruhi ekosistem laut baik flora maupun fauna. Penyu dan terumbu karang merupakan perwakilan dari flora dan fauna yang terdampak dari kondisi ekosistem laut. Sebagian besar jenis penyu terdapat di Indonesia dan Indonesia berada di segitiga terumbu karang sehingga terdapat diversifikasi terumbu karang yang tinggi. Namun, kondisi ini seringkali tidak disadari baik oleh masyarakat, wisatawan, maupun nelayan. Ruang Tumbuh untuk Penyu dan Terumbu Karang merupakan fasilitas konservasi untuk menambah ruang tumbuh bagi penyu dan terumbu karang dan dilengkapi dengan kegiatan pariwisata sebagai usaha untuk meningkatkan kesadaran masyarakat dan pengunjung akan pentingnya penyu dan terumbu karang bagi ekosistem laut. Proyek ini berlokasi di Pulau Kelapa dua, Kepulauan Seribu, Jakarta Utara. Dalam proyek ini, metode desain yang diterapkan adalah metode desain kamuflase untuk meningkatkan kenyamanan penyu dalam melakukan proses bertelur di area pantai. Dari metode ini terdapat beberapa poin penting yaitu alam, vegetasi, penglihatan, bentuk, dan warna. Penerapannya berdasarkan metode tersebut dapat dilihat melalui material yang alami sehingga menyatu dengan alam sekitar, vegetasi untuk meningkatkan potensi penyu bertelur dan mengkamuflase, serta bentuk melengkung untuk meniru penyu. Dengan begitu, dapat meningkatkan rasa cinta dan kesadaran manusia akan alam.